Merremia tuberosa (L.) Rendle-a New Record for Uttar Pradesh - Chandra, Veena (Indian Forester, 1982)
The paper represents Merremia tuberosa (L.) Rendle as a new record for Uttar Pradesh and furnishes Important Information regarding Its bablt, habitat and exact locality of occurrence.